English

If x = show thatdxdy2bt1+t2,y=a(1-t21+t2),show thatdxdy=-b2ya2x. - Mathematics and Statistics

Advertisements
Advertisements

Question

If x = `(2bt)/(1 + t^2), y = a((1 - t^2)/(1 + t^2)), "show that" "dx"/"dy" = -(b^2y)/(a^2x)`.

Sum

Solution

x = `(2bt)/(1 + t^2), y = a((1 - t^2)/(1 + t^2))`
Put t = tanθ.
Then x = `b((2tanθ)/(1 + tanθ)), y = a((1 - t^2)/(1 + tan^2θ))`
∴ x = b sin 2θ, y = a cos 2θ
∴ `x/b = sin2θ, y/a = cos2θ`

∴ `(x/b)^2 + (y/a)^2` = sin22θ + cos2

∴ `x^2/b^2 + y^2/a^2` = 1
Differentiating x and y w.r.t. y, we get
`(1)/b^2 xx 2x"dx"/"dy" + (1)/a^2 xx 2y` = 0

∴ `(2xdx)/(b^2dy) = (-2y)/a^2`

∴ `"dx"/"dy" = -(b^2y)/(a^2x)`

shaalaa.com
  Is there an error in this question or solution?
Chapter 1: Differentiation - Exercise 1.4 [Page 48]

RELATED QUESTIONS

Differentiate the following function with respect to x: `(log x)^x+x^(logx)`


 

if xx+xy+yx=ab, then find `dy/dx`.


Differentiate the function with respect to x.

`(sin x)^x + sin^(-1) sqrtx` 


Differentiate the function with respect to x.

`(x cos x)^x + (x sin x)^(1/x)`


Find `dy/dx` for the function given in the question:

yx = xy


If u, v and w are functions of x, then show that `d/dx(u.v.w) = (du)/dx v.w+u. (dv)/dx.w + u.v. (dw)/dx` in two ways-first by repeated application of product rule, second by logarithmic differentiation.


Differentiate w.r.t. x the function:

xx + xa + ax + aa, for some fixed a > 0 and x > 0


If cos y = x cos (a + y), with cos a ≠ ± 1, prove that `dy/dx = cos^2(a+y)/(sin a)`


If x = a (cos t + t sin t) and y = a (sin t – t cos t), find `(d^2y)/dx^2`


if `x^m y^n = (x + y)^(m + n)`, prove that `(d^2y)/(dx^2)= 0`


Find `dy/dx` if y = x+ 5x


Find `(d^2y)/(dx^2)` , if y = log x


Differentiate : log (1 + x2)  w.r.t. cot-1 x. 


If `"x"^(5/3) . "y"^(2/3) = ("x + y")^(7/3)` , the show that `"dy"/"dx" = "y"/"x"`


If log (x + y) = log(xy) + p, where p is a constant, then prove that `"dy"/"dx" = (-y^2)/(x^2)`.


If xy = ex–y, then show that `"dy"/"dx" = logx/(1 + logx)^2`.


`"If"  y = sqrt(logx + sqrt(log x + sqrt(log x + ... ∞))), "then show that"  dy/dx = (1)/(x(2y - 1).`


If ey = yx, then show that `"dy"/"dx" = (logy)^2/(log y - 1)`.


If x = 2cos4(t + 3), y = 3sin4(t + 3), show that `"dy"/"dx" = -sqrt((3y)/(2x)`.


If y = `log(x + sqrt(x^2 + a^2))^m`, show that `(x^2 + a^2)(d^2y)/(dx^2) + x "d"/"dx"` = 0.


If y = log (log 2x), show that xy2 + y1 (1 + xy1) = 0.


Find the nth derivative of the following : log (ax + b)


Find the nth derivative of the following : log (2x + 3)


If y = `25^(log_5sin_x) + 16^(log_4cos_x)` then `("d"y)/("d"x)` = ______.


If y = `log[4^(2x)((x^2 + 5)/sqrt(2x^3 - 4))^(3/2)]`, find `("d"y)/("d"x)`


If xy = ex-y, then `"dy"/"dx"` at x = 1 is ______.


If y = `("e"^"2x" sin x)/(x cos x), "then" "dy"/"dx" = ?`


Derivative of `log_6`x with respect 6x to is ______


`2^(cos^(2_x)`


`8^x/x^8`


If `f(x) = log [e^x ((3 - x)/(3 + x))^(1/3)]`,  then `f^'(1)` is equal to


Given f(x) = `log((1 + x)/(1 - x))` and g(x) = `(3x + x^3)/(1 + 3x^2)`, then fog(x) equals


Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×